THE ASSOCIATION OF AUTOIMMUNE THYROIDITIS WITH RHEUMATOID ARTHRITIS - Mohsen, Wisal Salman Abd (Al-Nahrain Journal of Science, 2010)
There has been controversy over the possible association of antithyroid with RA (Thyroiditiswith Rheumatoid Arthritis). We have therefore compared the prevalence thyroid antibody antithyroglobuline (anti-TG) and abnormal thyroid stimulating hormone (TSH) levels in 57 RA patientswith 20 aged matched control. 9 (16%) of the RA patients had thyroid Ab whereas no one ofcontrol had thyroid Ab (p<0.01). RA patients had TSH levels between (6-25 mU/L), while allcontrol group had TSH levels within normal range (p<0.01). These results suggests that RA isassociated with RA have minor hypothyroidism.